Valuing and revaluing education: what can we learn about measurement from the South African poor?. Issue 1 (2nd January 2017) - Clark, David A.
ABSTRACT: This paper reflects on the identification of relevant aspects of education for measurement purposes. It begins by reviewing some detailed lists of educational capabilities from disparate literatures. It then considers how ordinary South Africans perceive education by drawing on two open-ended surveys, and attempts to reconcile their views with different education lists. The main finding is that most abstract lists need to say more about the practical side of education (skills, information and knowledge for everyday living). They also need to embrace a more joined-up view of education that can incorporate linkages between different aspects of education and between education and other aspects of well-being (including mental states and material things). The final part of the paper makes the case for embracing the complexity and imprecision involved in measuring education and briefly sketches a methodological framework that can achieve this end.